Experimental Nuclear Astrophysics With the Light Elements Li, Be and B: A Review - Rapisarda, G.G.; Lamia, L.; Caciolli, A.; Li, Chengbo; Degl’Innocenti, S.; Depalo, R.; Palmerini, S.; Pizzone, R.G.; Romano, S.; Spitaleri, C.; Tognelli, E.; Wen, Qungang (Frontiers in Astronomy and Space Sciences, 2021)
Light elements offer an unique opportunity for studying several astrophysical scenarios from BBN to stellar physics. Understanding the stellar abundances of light elements is a key to obtain information on internal stellar structure and mixing phenomena in different evolutionary phases, such as pre-main-sequence (PMS), main-sequence (MS) or red-giant branch (RGB). In such a case, light elements lithium, beryllium and boron are usually burnt at temperatures of the order of 2-5 STX 106 K. Consequently, the astrophysical S(E)-factor and the reaction rate of the nuclear reactions responsible for the burning of such light elements must be measured and evaluated at ultra-low energies, between 0-10 keV. The Trojan Horse Method (THM) is an experimental technique that allows to perform this kind of measurements avoiding uncertainties due to the extrapolation and electron screening effects on direct data. A long THM research program has been devoted to the measurement of light element burning cross sections at astrophysical energies. In addition, dedicated direct measurements have been performed using both in-beam spectroscopy and the activation technique. In this review we will report the details of these experimental measurements and the results in terms of S(E)-factor, reaction rate and electron screening potential. A comparison between astrophysical reaction rates evaluated here and the literature will also be given.